Effects of upper cycle temperature on the actuation fatigue response of NiTiHf high temperature shape memory alloys. (1st October 2017) - Karakoc, O.; Hayrettin, C.; Bass, M.; Wang, S.J.; Canadinc, D.; Mabe, J.H.; Lagoudas, D.C.; Karaman, I.
Abstract: The present study focuses on the effects of upper cycle temperature (UCT) on the actuation fatigue response of nano-precipitation hardened Ni50.3 Ti29.7 Hf20 high temperature shape memory alloy (HTSMA). A series of actuation fatigue experiments were conducted under different constant tensile stresses while cycling temperature between two extreme martensitic transformation temperatures. The cyclic evolution of actuation strain and fatigue lives were monitored as a function of UCT and applied stress. The results revealed that the samples subjected to 300 °C UCT exhibit fatigue lives twice that of the samples with 350 °C UCT, and those tested under 300 MPa with 300 °C UCT withstand more than 10, 000 cycles with actuation strains of 2–3%. Actuation strains remained constant or increased with thermal cycling in the 350 °C UCT experiments, while those subjected to 300 °C UCT exhibited decreasing actuation strains, at all stress levels. In the 300 °C UCT experiments, partial martensitic transformation becomes operative, resulting in a reduction of actuation strain in each cycle, and postpones damage accumulation. In the 350 °C UCT cases, increase of actuation strain is attributed to the partial recovery of cyclically-induced remnant deformation at higher temperatures and as a result, larger volume of transforming material. This, in turn, accelerates the formation of cracks, that open and close during thermal cycling and reversible martensitic transformation, and manifests itself as additional recoverable strain in each cycle. Overall, the current work constitutes the first study on actuation fatigue response of HTSMAs and an important step towards understanding microstructure - fatigue performance relationship in these alloys. Graphical abstract: Nano-precipitation hardened NiTiHf high temperature shape memory alloys exhibit excellent cyclic actuation stability and actuation work outputs as high as or higher than binary NiTi shape memory alloys. Image 1